Four-Tier Test Model to Measure Prospective Physics Teacher Students’ Multiple Representation Ability on Electricity Topic - Rahmawati Rahmawati; Widiasih Widiasih; Nasrah Nasrah; A. Muafiah Nur; Dewi Hikmah Marisda (STKIP Singkawang, 2022)
The advantage of four-tier model test is that it has four levels of questions that require complex reasoning abilities from students to express the reasons for their answers to the problems given. This study aimed to develop a multiple representation test with a four-tier model to measure students’ multiple representation in electricity topics. The stages of developing this test instrument used a stage model of The Design Based Research which consists of five stages, namely developing an assessment framework, designing items, developing rubrics, conducting trials, and applying the Racsh Model analysis with the Item Response approach. Theory (IRT) program assisted Winsteps version 3.68.2. The research method used was descriptive-exploratory method to describe the results of the development and validation of four-tier model test. This test consisted to 20 items were developed based on four types of representation, namely verbal representations, diagrammatic representations (pictures), mathematical representations, and graphic representations with each indicator. The research subjects involved were 30 prospective physics students at the pilot test stage and 79 prospective physics students at the field test stage from different universities in Makassar city. The results of the development of the four-tier test model test overall items are valid with a high level of reliability (Cronbach's Alpha value = 0.80). Based on the results of expert judgment validation and testing, it can be concluded that the multiple representation test with four-tier model on electricity topic is feasible to use.